The Effect Of Spraying Enzylaw Liquid Organic Fertilizer (Poc) On Crop Production Allium fistulosum L. - Pantow, Wilhelm (Sam Ratulangi University, 2024)
This research aims to determine the effect of enzylaw liquid organic fertilizer (POC) on the production of spring onions (Allium fistulosum L.). The research method used was the Completely Randomized Design (CRD) method because the experimental media/materials were homogeneous or uniform. Consists of 6 treatments, as follows; A: Control, B: 1 ml enzyme/1 liter of water, C: 2 ml enzyme/1 liter of water, D: 3 ml enzyme/1 liter of water, E: 4 ml enzyme/1 liter water, F: 5 ml enzyme/1 liter of water. This research activity was carried out from January to March 2023 in Paslaten Village, East Tomohon District. The results of the research showed that the use of Enzylaw liquid organic fertilizer (POC) had an effect on the growth of leek plants. Giving POC enzylaw at a dose of 5 ml of enzyme/1 liter of water produces on average: (1) The highest number of stems (134 stems), (2) Produces the highest average number of leaves, namely 375 leaves, and (3) Produces an average of the highest average wet weight, namely 4823 g. Keywords: liquid organic fertilizer (POC), Enzylaw, Allium fistulosum L. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh pupuk organik cair (POC) enzylaw terhadap produksi bawang daun (Allium fistulosum L.). Metode penelitian yang digunakan yaitu metode Rancangan Acak Lengkap (RAL), karena media/bahan percobaan homogen atau seragam. Terdiri atas 6 perlakuan, sebagai berikut ;A : Kontrol, B : 1 ml enzylaw/1 liter air, C : 2 ml enzylaw/1 liter air, D : 3 ml enzylaw/1 liter air, E : 4 ml enzylaw/1 liter air , F : 5 ml enzylaw/1 liter air. Waktu kegiatan penelitian ini dilaksanakan pada bulan Januari sampai Maret 2023 di Kelurahan Paslaten Kecamatan Tomohon Timur. Hasil penelitian menunjukkan bahwa penggunaan pupuk organik cair (POC) enzylaw berpengaruh terhadap petumbuhan tanaman bawang daun. Pemberian POC enzylaw dengan dosis 5 ml enzylaw/1 liter air menghasilkan rata-rata: (1) Jumlah batang terbanyak (134 batang), (2) Menghasilkan rata-rata jumlah daun terbanyak, yaitu 375 helai, dan (3) Menghasilkan rata-rata berat basah tertinggi, yaitu 4823 g. Kata kunci: POC, Enzylaw, Allium fistulosum L.